Homoarginine and creatine deficiency do not exacerbate murine ischaemic heart failure - McAndrew, DJ; Lake, HA; Zervou, S; Schwedhelm, E; Schneider, JE; Neubauer, S; Lygate, CA (Wiley, 2022)
Aims Low levels of homoarginine and creatine are associated with heart failure severity in humans, but it is unclear to what extent they contribute to pathophysiology. Both are synthesized via L-arginine:glycine amidinotransferase (AGAT), such that AGAT−/− mice have a combined creatine and homoarginine deficiency. We hypothesized that this would be detrimental in the setting of chronic heart failure.